ENHANCING LISTENING COMPREHENSION THROUGH PODCASTS AND ONLINE RESOURCES FOR A2 STUDENTS - Odilkhon Abduvokhidov, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract: Listening comprehension is widely recognized as one of the most challenging skills for A2 learners of English. At this proficiency level, learners are expected  to  understand  short,  slow-paced  utterances  on  familiar  topics,  yet  often struggle to extract meaning from authentic input. Recent technological advances have made  podcasts  and  online  resources  easily  accessible,  offering  multimodal  and interactive support for language development. This paper investigates how podcasts and  online  listening  tools  can  be  integrated  into  A2-level  English  classrooms  to enhance  listening  comprehension.  Drawing  on  systematic  literature  review  and thematic  analysis  of  recent  studies  (2005–2024),  the  article  identifies  pedagogical strategies,  scaffolding  techniques,  and  assessment  models  for  effective implementation.  Findings  reveal  that  podcasts,  when  combined  with  pre-listening scaffolds, comprehension checks, transcripts, and post-listening communicative tasks, significantly improve learners’ decoding skills, vocabulary retention, and confidence. Online  resources  further  support  personalization,  multimodal  engagement,  and autonomous  learning.  The  paper  concludes  with  practical  recommendations  for teachers, highlights current limitations in research on low-level learners, and suggests future directions.